An Economics Academic Word List (EAWL): Using online resources to develop a subject-specific word list and associated teaching-learning materials - O’Flynn, James Adam (Journal of Academic Language and Learning, 2019)
The Academic Word List (AWL) (Coxhead, 2000) is widely used by educators providing Academic Language and Learning (ALL) development in tertiary education settings. The AWL, though, has been criticised for failing to take sufficient account of disciplinary variation, and for relying on the archaic General Service List (West, 1953). This study, therefore, describes the process of using readily available online resources to develop an academic word list that is subject-specific, and based on the New General Service List (Browne, Culligan, & Phillips, 2014). The resulting list, the Economics Academic Word List (EAWL), comprises 887 words (or 1,763 word forms), which cover up to 5.6% of texts both received and produced by university-level economics students. It is argued that, in comparison with generic academic word lists, the EAWL serves as a better reference for developing the academic language of the economics discourse community. This leads to a series of implications and the introduction of a dedicated EAWL website, hosting a range of ready-made teaching-learning materials.